Policy Brief - Unlocking Potential: Addressing Challenges and Harnessing the Role of Cottage Industries, Insight from Oromia Region of Ethiopia - Birku Reta Entele; Yadeta Chimdessa; Mogos Tufa; Hailu Beyecha; Milkessa Seyoum (Ethiopian Journal of Science and Sustainable Development, 2025)
Executive Summary